2021
DOI: 10.1111/cpr.13143
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in cell cycle regulation: Mechanisms to clinical significance

Abstract: Circular RNAs (circRNAs), a type of non‐coding RNA, are single‐stranded circularized molecules characterized by high abundance, evolutionary conservation and cell development‐ and tissue‐specific expression. A large body of studies has found that circRNAs exert a wide variety of functions in diverse biological processes, including cell cycle. The cell cycle is controlled by the coordinated activation and deactivation of cell cycle regulators. CircRNAs exert mutifunctional roles by regulating gene expression vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 126 publications
0
18
0
Order By: Relevance
“… 222 CircRNAs are stable in multiple tissues and body fluids. 217 , 223 They lack protein encoding capacity and they have a closed loop structure. 224 Recent studies have revealed the role of circRNAs in HCC.…”
Section: Beta-catenin and Hepatocellular Carcinomamentioning
confidence: 99%
“… 222 CircRNAs are stable in multiple tissues and body fluids. 217 , 223 They lack protein encoding capacity and they have a closed loop structure. 224 Recent studies have revealed the role of circRNAs in HCC.…”
Section: Beta-catenin and Hepatocellular Carcinomamentioning
confidence: 99%
“…CircRNAs are formed by splicing of precursor mRNAs (pre-mRNAs) and are mostly endogenous. They have no 3′ tail or 5′ cap end and are covalently closed loops ( Qu et al, 2015 ; Meng et al, 2017 ) formed by lasso-driven cyclization, direct reverse splicing, or exon skipping, or they can be cyclized by intron pairing ( Wang et al, 2021e ; Xiao et al, 2021 ). In addition, circRNAs can also be formed by RNA binding proteins (RBPs)-mediated cyclization joining the downstream 5′ end donor site to the upstream 3′ end acceptor site to form a single-stranded covalent closed-loop that joins the remaining sequence after removal of the intron ( Ali et al, 2021 ; Wang et al, 2021d ).…”
Section: Overview and Biological Properties Of Circular Rnamentioning
confidence: 99%
“…Many circRNAs that are highly expressed in blood have relatively low expression of their corresponding linear RNAs ( Rahmati et al, 2021 ; Xiao et al, 2021 ). The unique functions and properties of circRNAs make them of great clinical potential in life sciences and medicine ( Gu et al, 2021 ; Yi et al, 2021 ).…”
Section: Roles and Significance Of Circrnas In Pediatric Malignant Solid Tumorsmentioning
confidence: 99%
“…Exosomes, small EVs, play a crucial role in intercellular communication by transporting proteins, mRNAs, and ncRNAs [2]. In the past decade, ncRNAs, including mi-croRNAs (miRNAs), PIWI-interacting RNAs (piRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs), have been intensively studied in many human diseases, particularly cancers [3][4][5][6]. Studies have indicated that exosomal ncRNAs acting as versatile regulators at the transcriptional and post-transcriptional levels may contribute to cancer progression and metastasis [7,8].…”
Section: Introductionmentioning
confidence: 99%